FDG PET for Gauging of Sarcoid Disease Activity - Adams, Human; Keijsers, Ruth G.; Korenromp, Ingrid H. E.; Grutters, Jan C. (Seminars in Respiratory and Critical Care Medicine, 2014)
Fluorodeoxyglucose (FDG), labeled with a positron emitting fluorine-18 (18F), is a synthesized glucose analogue and is well known for its application in a wide variety of clinical conditions such as cancer. Visualizing metabolic activity of inflammation is another application of FDG in positron emission tomography (PET). Here, active granulomas appear to have a high affinity for FDG, which is reflected in a high sensitivity of FDG PET imaging. This has led to novel applications of FDG PET in sarcoidosis diagnosis and management. Although chest radiography and high-resolution computed tomography are still the cornerstones of diagnosing pulmonary involvement, FDG PET appears to be superior to both techniques in imaging active sites of disease. FDG PET also correlates well with serum biomarkers such as soluble interleukin-2 receptor in symptomatic patients, and even visualizes active lesions in the context of normal serum biomarkers. Moreover, FDG PET activity in lung parenchyma correlates with decrease of lung function values over time. Also in cardiac involvement in sarcoidosis, FDG PET is a promising technique complementary to magnetic resonance imaging, especially in guiding treatment. New developments, such as applications for quantitative organ-specific measurement, are proceeding and will probably enhance the clinical implementation of FDG PET in sarcoidosis.
Keywords: fluorodeoxyglucose; PET/CT; sarcoidosis; biomarker; pulmonary function test; imaging; cardiac; treatment monitoring; SUV